Mise en place d’un dispositif de formation hybride : une innovation c'est un changement qui a réussi ? - Fatiha TALI (Éducation et Socialisation)
In this thematic review on innovation, our article aims to study the processes implemented during a pedagogical innovation in a hybrid training context. Starting from a theoretical framework referring to the sociocognitive approach, we seek to see how collective agency could be an engine of innovation. For this, in a first part, the theoretical framework makes it possible to approach the processes linked to the development of a hybrid training system as well as the collective arrangement. In a second part, the methodological framework linked to the study of a concrete case of innovation processes is described with both the research approach and the pedagogical engineering approach implemented. The third part presents the results of the changes in three areas: training modalities, institutional practices and learners' learning modalities.